Overweight and obesity in Portugal : national prevalence in 2003–2005 - Carmo, Isabel Do (2012)
Obesity is an endemic health problem in most developed countries, requiring serious public health attention. The first Portuguese nationwide representative survey about obesity (with objective anthropometric measurement) was undertaken from 1995 to 1998. This paper presents data coming from the second and most recent nationwide representative study of obesity, with objective measurement of weight, height, waist and hip circumferences. Data were collected between January 2003 and January 2005. The survey collected objective body mass index (BMI) values of 8116 participants aged 18–64. Main findings were: 2.4% of the sample had low weight (BMI < 18.5), 39.4% were overweight (BMI between 25.0 and 29.9), and 14.2% obese (BMI 30). Waist circumference measurement showed that 45.6% of the sample suffers increased cardiovascular health risks associated with high waist circumference. The overall overweight/ obesity prevalence increased from 49.6% (in 1995–1998) to 53.6% (in 2003–2005). These data suggest that although obesity was identified as a public health problem one decade ago, action to reduce it does not seem to have been very effective to date. Well-defined public health intervention must be targeted to specific population groups where higher levels of obesity prevalence were found: low socioeconomic level groups and low-education level groups.